2009
DOI: 10.1002/mar.20294
|View full text |Cite
|
Sign up to set email alerts
|

Modeling consumer adoption of mobile shopping for fashion products in Korea

Abstract: This study explores the potential of a consumer technology adoption model in examining structural relationships among mobile commerce characteristics, perceived value, and intention to adopt mobile shopping for fashion products. Through an online survey method, the 511 valid questionnaires obtained from Korean users of a mobile Internet service identified perceived m-commerce characteristics consisting of four factors: usefulness, enjoyment, ease of use, and instant connectivity. The first three factors were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
222
1
13

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 294 publications
(249 citation statements)
references
References 44 publications
13
222
1
13
Order By: Relevance
“…12,13 Three items measuring attitude and five items measuring adoption intention were adapted from consumer behavioural intention studies. 44,45 To measure consumer traits such as innovativeness and market mavenism, a three-item consumer innovativeness scale, 22 and a six-item market mavenism scale 39 were adapted and used. The wording of each item was modified to suit the purpose of this research.…”
Section: Methodology Of Researchmentioning
confidence: 99%
“…12,13 Three items measuring attitude and five items measuring adoption intention were adapted from consumer behavioural intention studies. 44,45 To measure consumer traits such as innovativeness and market mavenism, a three-item consumer innovativeness scale, 22 and a six-item market mavenism scale 39 were adapted and used. The wording of each item was modified to suit the purpose of this research.…”
Section: Methodology Of Researchmentioning
confidence: 99%
“…Interactivity is one aspect of channel accessibility, and it greatly influences the amount of effort that a user puts forth. Ko et al (2009) found that instant connectivity was positively associated with the perceived value of mobile web shopping for fashion products. In the context of mobile web shopping, the m-channel is perceived as a useful means of distribution if it offers ease of use, a high degree of interactivity, ease of information customization, and convenient access.…”
Section: M-accessibility Utilitymentioning
confidence: 98%
“…Researchers interested in m-commerce have used quantitative approaches to investigate topics such as adoption of m-shopping (Kim, Ma, & Park, 2009;Ko, Kim, & Lee, 2009), general attitudes toward m-commerce (Bigné, Ruiz, & Sanz, 2007), and perceived m-service value (Gummerus & Pihlstrom, 2011). To develop mobile web shopping in an effective manner, information concerning the type of m-consumer who wants to integrate m-shopping into their consumption behaviors would be useful.…”
Section: Introductionmentioning
confidence: 99%
“…To date, most studies that have examined consumer behavior in the clothing mobile commerce focus on the factors that have led to their adoption (Hahn and Kim, 2013;Kim, Ma, and Park, 2009;Ko, Kim, and Lee, 2009). Accepting that clothing mobile purchasing is not a remote factor, we believe that it is necessary to go a step further in the analysis of consumer behavior to analyze the determining factors in maintaining long term consumer-seller relationship.…”
Section: Theoretical Frameworkmentioning
confidence: 99%